Hepatocellular Carcinoma cells: activity of Amygdalin and Sorafenib in Targeting AMPK /mTOR and BCL-2 for anti-angiogenesis and apoptosis cell death - Tarek El-Sewedy; Afrah Fatthi Salama; Amro E. Mohamed; Nashwa M. Elbaioumy; Ali H. El-Far; Aisha Nawaf Albalawi; Alaa Elmetwalli (BMC, 2023)
Abstract Background Sorafenib (Sor) is the only approved multikinase inhibitor indicated for the treatment of HCC. Previous studies have shown that amygdalin (Amy) possesses anticancer activities against several cancer cell lines; we suggested that these compounds might disrupt AMPK/mTOR and BCL-2. Therefore, the current study used integrated in vitro and in silico approaches to figure out Amy and Sor's possible synergistic activity in targeting AMPK/mTOR and BCL-2 for anti-angiogenesis and apoptosis cell death in HepG2 cells. Results Notably, Amy demonstrated exceptional cytotoxic selectivity against HepG2 cells in comparison to normal WI-38 cells (IC50 = 5.21 mg/ml; 141.25 mg/ml), respectively. In contrast, WI-38 cells were far more sensitive to the toxicity of Sor. A substantial synergistic interaction between Amy and Sor was observed (CI50 = 0.56), which was connected to cell cycle arrest at the S and G2/M stages and increased apoptosis and potential necroptosis. Amy and Sor cotreatment resulted in the highest glutathione levels and induction of pro-autophagic genes AMPK, HGMB1, ATG5, Beclin 1, and LC3, suppressed the mTOR and BCL2 anti-apoptotic gene. Finally, the docking studies proposed that Amy binds to the active site of the AMPK enzyme, thus inhibiting its activity. This inhibition of AMPK ultimately leads to inhibition of mTOR and thus induces apoptosis in the HepG2 cells. Conclusion Although more in vivo research using animal models is needed to confirm the findings, our findings contribute to the evidence supporting Amy's potential anticancer effectiveness as an alternative therapeutic option for HCC.